Factors affecting urine EIA sensitivity in the detection of Chlamydia trachomatis in men. Issue 2 (April 1994) - Talbot, H; Romanowski, B
Abstract : OBJECTIVE–This study examined the effects of four variables on the detection of Chlamydia trachomatis in urine from men by enzyme immunoassay (EIA). These variables were: symptoms and signs of urethritis, urine polymorphonuclear leucocytes (PMN), inclusion counts from urethral chlamydia cell cultures and the time between testing and last voiding. METHODS–Included were patients with and without symptoms and/or signs of urethritis attending the Edmonton Sexually Transmitted Disease Clinic. Men were asked to submit a 20 ml volume urine sample. Urethral swabs were collected for gram stain, chlamydia and gonorrhea culture. RESULTS–A total of 318 men were evaluated of whom 47 had chlamydia. Excluding six men who were coinfected with gonorrhoea, sensitivities and specificities of the Microtrak, Chlamydiazyme and IDEIA systems were 78.1% and 99.6%, 75.6% and 100%, and 80.5% and 97.8% respectively. Last void time did not affect the sensitivity. However, sensitivity was best when applied to men with severe evidence of urethritis. CONCLUSION–There is evidence that urine EIA could be used to detect chlamydia in men with acute urethritis but not in those without signs of urethritis.